Communities of wood‐inhabiting bryophytes and fungi on dead beech logs in Europe – reflecting substrate quality or shaped by climate and forest conditions?. (19th August 2014) - Heilmann‐Clausen, Jacob; Aude, Erik; van Dort, Klaas; Christensen, Morten; Piltaver, Andrej; Veerkamp, Mirjam; Walleyn, Ruben; Siller, Irén; Standovár, Tibor; Òdor, Péter; Linder, Peter
Abstract Aim Fungi are drivers of wood decay in forested ecosystem, while bryophytes use dead wood as a platform for their autotrophic lifestyle. We tested the hypothesis that fungal communities on beech logs are mainly structured by substrate quality, while bryophyte communities are structured by climatic gradients. In addition, we tested whether community structure in both organism groups is altered along a gradient from nearly pristine forest to forests heavily affected by management and human disturbance in the past. Location Europe. Methods We surveyed 1207 fallen beech logs in 26 of the best‐preserved forest stands across six European countries, representing a gradient in overall naturalness of the forest landscape. Recorded species were classified into ecological guilds. Indirect ordination and variation partitioning was used to analyse the relationship between species composition and environmental variables, recorded at log or site level. Results In total, 10, 367 bryophyte and 15, 575 fungal records were made, representing 157 and 272 species, respectively. Fungal communities were more clearly structured by substrate quality than were bryophyte communities. In both groups a distinct turnover in species composition was evident along a longitudinal gradient from Central to Western Europe. Fungi specialized in trunk rot and specialized epixylic bryophytes were scarcely represented in Atlantic regions, and partly replaced by species belonging to less specialized guilds. Variables related to climate and forest conditions were confounded along this main geographical gradient in community composition. Main conclusions We found that bryophyte and fungal communities co‐occurring on fallen beech logs in European beech forest reserves differed in their responses to biogeographical drivers and local‐scale habitat filters. Both groups responded to major gradients in climate and forest conditions, but the loss of specialist guilds in degraded forest landscapes points to a functionally important effect of forest landscape degradation at the European continental scale.